Fiscal Deficit and Public Debt in Industrial Countries, 1970-1994 - Fanizza, Domenico (IMF Working Papers; Working Paper ;, 1995)
This paper assembles a set of relevant fiscal data, for both the individual countries and for the aggregate G-7 and 18 industrial countries, which covers a period long enough to allow an assessment of trends and the conduct of econometric tests. The 'world' fiscal deficit has been rising since the 1970s and reached a historic high in 1993-94; the rise of the deficit has been accompanied by a significant decline in world saving. The paper argues that the increase in public debt, which has been the consequence of the accumulation of the fiscal deficits, has pushed up worldwide interest rates. Econometric evidence in support of this relationship is presented on the basis of panel data for the period 1970-93.